PENYUSUNAN ZONA KONSERVASI DAN PEMANFAATAN AKUIFER BEBAS PADA CEKUNGAN AIRTANAH PAGATAN KABUPATEN TANAH BUMBU, KALIMANTAN SELATAN - Agus Harjanto; Thomas Triadi Putranto; Widyanto David (TATALOKA, 2019)
Pagatan groundwater basin is located on Tanah Bumbu Regency, South Kalimantan Province with 506.714 Ha or 13,5%  from South Kalimantan total area. The increasing of population also affect the water demand as a human primary need. As one of the best sources for clean water, groundwater is being intensively extracted to fulfill the need of clean water until it becomes uncontrollable and damage the supply and demand equilibrium. This groundwater extraction has been turning uncontrollaby and decreasing the quantity and quality of groundwater. The purpose of this study is to know the water tables, to know the quality of groundwater, to determine the category of conservation zone and areas to be protected, and suitability of spatial planning of the region with conservation zone of research area. The method for this research is qualitative observation and descriptive. The method of observation is the measurement of water table, and sampling of wells, while the method of analysis is data processing which is done based on primary and secondary data obtained on field research data to determine the zone of conservation and groundwater utilization in in research area.The result showed that unconfined groundwater aquifers have groundwater flow pattern spreading flow towards South and Southwest. From the 150 groundwater samples, there are 9 samples that do not meet the requirements for drinking water.The construction of groundwater conservation zone is based on groundwater availability factor, the similarity of groundwater damage.